Measurement of Childhood Poverty in the United States and Its Enduring Influences - Yang, Zi (2019)
This paper measures childhood poverty in the United States and classifies it into three degrees based on different durations – persistent poverty, chronic transient poverty, and non-chronic transient poverty – using the Panel Study of Income Dynamics (PSID) data and actual poverty thresholds in the United States. Then I examine the enduring influences of different types of childhood poverty on future performance, including academic achievement, income, and criminal behavior, utilizing OLS and logistic models as well as Mincer wage functions. The regression results show that childhood poverty has a negative impact on schooling years and earnings. Living in poverty increases the likelihood of committing criminal behavior. In addition, longer spells of childhood poverty, especially persistent poverty, are shown to have stronger enduring influences compared with other types of childhood poverty. Meanwhile, while no prior studies examine the impact of short-term childhood poverty, this study shows that even short a duration of childhood poverty (non-chronic transient poverty) is associated with shorter school years completed and a higher risk of committing crime. However, it has no significant impact on adult earnings